Improving the use of intravenous antihypertensive medications in the hospital setting: a quality improvement initiative for patient safety. Issue 4 (27th November 2019) - Salman, Jacob; Salman, Alicja; Kumar, Sarwan; Gjeka, Rudin; Tegeltija, Vesna; Peterson, Daymon; Chams, Nour; Ross, Ian
Abstract : Intravenous (IV) hydralazine, enalapril and labetalol are oftentimes used without indication for the treatment of asymptomatic hypertension in the hospital setting and have been shown to have substantial adverse effects that are associated with increased morbidity and mortality, as well as longer length of stay. Their use is also associated with greater monetary costs. In this project, we studied the frequency of use and consequences of these medications before and after a series of education cycles which clarified when and when not to use intravenous antihypertensives (IVAHs). Our initial aim was to decrease the unindicated use of IVAH by at least 25% in the setting of asymptomatic hypertension in our community hospital within a 1-year period after introducing education on the topic. Multidisciplinary involvement throughout three Plan-Do-Study-Act (PDSA) cycles yielded favourable results. We focused on education towards a hospital-wide knowledge gap stemming from a lack of guidelines regarding the treatment of asymptomatic hypertension, as well as the guideline indications for IVAH. After three cycles of education targeting different groups, the unindicated use of IVAH fell by a total of 66%, decreasing patient exposure by approximately 248 cases over the total course of the study and ultimately, yielding a 52% increase in patient safety. Secondary outcome included a reduction in cost. It was noted that IV drugs cost more than their oral counterparts. The culture change in switching away from IVAH unless otherwise indicated was driven by repetitive education and group discussion to close the gap created by a lack of guidelines.